Meningitis in a School-Aged Child due to Haemophilus influenzae Type E during the Post-Conjugate Vaccine Era—Monroe County, NY, 2011 - Byron S. Kennedy; Anita C. Weimer; Brenden Bedard; Jennifer L. Nayak; Drew Sacheli; John Ricci; Donna D. Meyer; Donna Hubbard (Vaccines, 2014)
In late October 2011, the Monroe County Department of Public Health (MCDPH) was notified of a suspected case of meningitis in a 9-year old girl from Monroe County, NY. Laboratory testing at the New York State Department of Health (NYSDOH) Wadsworth Center confirmed the identification of Haemophilus influenzae serotype e (Hie) isolated from the patient’s cerebrospinal fluid (CSF) using real-time polymerase chain reaction (RT-PCR). The universal immunization of infants with conjugate H. influenzae type b (Hib) vaccine has significantly reduced the incidence of invasive Hib disease, including meningitis, one of the most serious complications for infected children. Not surprisingly, as the epidemiology of invasive H. influenzae continues to change, non-Hib serotypes will likely become more common. The findings reported here underscore the importance for clinicians, public health officials, and laboratory staff to consider non-Hib pathogens in pediatric cases of meningitis, especially when initial investigations are inconclusive.